The role of the TGF-β1 signaling pathway in the process of amelogenesis - Ma, Xiaoxue; Ma, Yunjing; Lin, Zhiyong; Ji, Mei (Frontiers in Physiology, 2025)
Amelogenesis is a highly regulated process involving multiple signaling pathways, among which the transforming growth factor-β1 (TGF-β1) signaling pathway plays a pivotal role in enamel formation. This review firstly elucidates the critical functions of TGF-β1 in regulating ameloblast behavior and enamel development, encompassing ameloblast proliferation, differentiation, apoptosis, enamel matrix protein synthesis, and mineralization. Secondly, based on emerging evidence, we further discuss potential interactions between TGF-β signaling and circadian regulation in enamel formation, although this relationship requires further experimental validation. Finally, future research directions are proposed to further investigate the relationship between TGF-β1 and the circadian clock in the context of amelogenesis.